2003
DOI: 10.1079/ber2003248
|View full text |Cite
|
Sign up to set email alerts
|

Navigation of Lutzomyia longipalpis (Diptera: Psychodidae) under dusk or starlight conditions

Abstract: The responses of male and female Lutzomyia longipalpis (Lutz & Neiva) to different wavelengths of light was tested by presenting the sandflies with two light sources simultaneously, a series of test wavelengths between 350-670 nm and a 400 nm control. To test whether L. longipalpis could discriminate between the test and control, three sets of experiments were carried out in which the test wavelengths were presented at higher, equivalent or lower intensity than the control. In all three experiments, ultra-viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
2
28
0
1
Order By: Relevance
“…It is interesting that color is the only factor that inßuences whiteßy landings on plant and nonplant surfaces van Lantern 1976, van Lantern andWoets 1977). In a study conducted by Mellor and Hamilton (2003), a greater percentage of Lu. longipalpis was attracted toward 490 Ð546-nm than 400-nm wavelength light at lower, equivalent, and higher light intensities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is interesting that color is the only factor that inßuences whiteßy landings on plant and nonplant surfaces van Lantern 1976, van Lantern andWoets 1977). In a study conducted by Mellor and Hamilton (2003), a greater percentage of Lu. longipalpis was attracted toward 490 Ð546-nm than 400-nm wavelength light at lower, equivalent, and higher light intensities.…”
Section: Discussionmentioning
confidence: 97%
“…longipalpis respond maximally to light in the UV region and blue-green-yellow region (Mellor et al 1996). Mellor and Hamilton (2003) provided evidence that Lu. longipalpis is more attracted to UV, blue, green, and yellow wavelengths and were able to discriminate between wavelengths independent of intensity.…”
mentioning
confidence: 97%
“…However, the effect of the darkness on the blood feeding frequency is more difficult to explain. The most likely explanation is that the moonlight helps sand flies to navigate and to find its host (Mellor & Hamilton 2003). Further studies under more controlled conditions are needed to understand the effects of moonlight intensity observed in this and other studies.…”
mentioning
confidence: 98%
“…They are mostly nocturnal and in the light of existing knowledge one might expect these vectors to be affected by the lunar cycle (Chaniotis et al 1971, Mellor & Hamilton 2003.…”
mentioning
confidence: 99%
“…Whereas incandescent bulbs produce a broad spectrum of light to attract insects, LEDs can be selected to emit a narrow bandwidth or specific color. Previous studies have found that mosquitoes (Wilton andFay 1972, Burkett andButler 2005), phlebotomine sand flies (Mellor and Hamilton 2003), and Culicoide flies (Bishop et al 2004) are attracted preferentially to specific wavelengths of light. Finally, LED bulbs are advantageous in that they can be changed quickly in the field to configure the trap to the particular needs of a trapping environment.…”
mentioning
confidence: 99%